Traits profiling and genotype selection in common bean (Phaseolus vulgaris L.) in Ethiopia using the GT and GYT biplot analyses - Abebe, Tefera; Fenta, Berhanu Amsalu; Setotaw, Tesfahun Alemu; Mukankusi, Clare; Tumesa, Kidane; Feyissa, Tileye (Wiley, 2025)
Phaseolus vulgaris, a crucial legume worldwide, is essential for human consumption and provides an abundant supply of pro teins, micronutrients, antioxidants, and bioactive compounds. A common bean breeder faces considerable challenges due to inherent trade- offs when attempting to simultaneously improve grain yield, Fe/Zn concentrations, and disease resistance. In this study, 118 common bean genotypes, along with two standard check cultivars, were evaluated using a randomized complete block design with a row- column arrangement, with two replicates in two locations during the Meher season in 2019/20. In our study, GT and GYT analyses were used to dissect the associations between various traits and to select superior genotypes based on multiple traits. The highest grain yield t ha−1 was obtained from genotypes G18, G63, and G81. The assessed genotypes showed Fe concentration ranging from 41.4 to 89.4 ppm, with a mean of 51.6 ppm, whereas Zn concentration ranged from 17.7 to 37.2 ppm, with a mean of 24.5 ppm. The GT biplot explained 43.8% of the total variation, identifying donor genotypes with high Fe/Zn concentrations and disease resistance, whereas the GYT biplot accounted for 80.4% of the variation and revealed 10 high- performing, balanced genotypes. Positive correlations were observed between yield and plant height, Fe and Zn concentrations, and days to flowering and maturity, indicating the potential for simultaneous improvement in yield, micronutrient density, and disease resistance. Overall, the integration of GT and GYT biplot analyses enabled the identification of promising candidate gen otypes for direct release (G63, G100, G81, G80, and G18) and trait- specific donors for crossing, offering a practical strategy for the development of biofortified bean cultivars with high yield and disease resistance.